Health Workforce Challenges: Key Findings From the Swiss Cohort of Healthcare Professionals and Informal Caregivers (SCOHPICA) - Vladimir Jolidon; Jonathan Jubin; Jonathan Jubin; Emilie Zuercher; Leonard Roth; Tania Carron; Annie Oulevey Bachmann; Annie Oulevey Bachmann; Ingrid Gilles; Ingrid Gilles; Isabelle Peytremann-Bridevaux (Frontiers Media S.A., 2024)
ObjectivesThe Swiss Cohort of Healthcare Professionals and Informal Caregivers (SCOHPICA) was created to study the career trajectories, retention intentions, and wellbeing of healthcare professionals (HCPs), addressing challenges such as staff turnover, low job satisfaction and burnout.MethodsSCOHPICA is a prospective open cohort. An electronic questionnaire was used to collect data from HCPs across multiple healthcare settings in Switzerland, encompassing the intention to stay in the profession, wellbeing, and various organizational, psychosocial, occupational and sociodemographic determinants.ResultsThe first (2022) baseline sample included 1707 HCPs from over 20 professions. Notably, 13% did not intend to stay in their profession, with intermediate caregivers (24%), registered nurses (17%) and pharmacists (17%) reporting the highest rates. Pharmacists scored lowest in wellbeing. Across determinants, pharmacists, physicians, and registered nurses reported worse scores for workload and work-life balance. Nursing professions had lower scores in various determinants, including influence at work, staffing and resource adequacy, and possibilities for development.ConclusionSCOHPICA will provide critical insights on HCPs' work conditions and experiences, supporting health workforce monitoring and management, and informing policy-making to ensure high-quality healthcare delivery.